PEMBINAAN KOMPETENSI PROFESIONAL GURU OLEH KEPALA SEKOLAH DALAM PELAKSANAAN PENELITIAN TINDAKAN KELAS DI SMP NEGERI 1 MUTIARA KABUPATEN PIDIE - Mansur .; Yusrizal .; Niswanto . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
Abstract[Z1]                The implementation of the classroom action research greatly helps teachers in solving learning obstacles. The purposes of this study are to investigate: The purpose of this research is to get information about how to develop professional competence of teachers by the principal in the implementation of classroom action research at SMP Negeri 1 Mutiara. This study used thedescriptive qualitative method; data collection techniques used were observation, interviews and documentation study; and research subjects were the school principal and the teachers. The data analysis was done by reducing the data and displaying the data. The results of this study showed that the principal had implemented: 1) programs that had been planned, that is, the preparation of an annual program and the semester program by involving all subject teachers; 2) the training of the classroom action research for teachers and reprimand the teachers who did not participate actively ; and 3) a follow-up activity by requiring teachers to partake Teacher Professional Development Networks(MGMPs) regularly with the expectation that the obstacles encountered in training activities can overcome and guide the teacher wisely, that is, by reprimanding well, directing, and developing teachers who have problems with professional competence in conducting action research so that the ability to make reports  of the classroom action research is successful.Keywords : Teacher Professioanl Development and Research Action Class [Z1]Abstrak terlalu panjang krn ketentuannya abstrak hanya terdiri dari 100-200 kata saja.